2008
DOI: 10.1002/mds.22106
|View full text |Cite
|
Sign up to set email alerts
|

Burden, perceived health status, and mood among caregivers of Parkinson's disease patients

Abstract: The objective of this study is to describe the characteristics of the caregivers of patients with Parkinson's disease (PD) and to analyze the association between these characteristics and caregiver burden, perceived health and mood status, and identify their predictors. A multicenter, nationwide, observational, cross-sectional study that included 289 patient-caregiver pairs was conducted. Caregiver self-assessments were the Hospital Anxiety and Depression Scale (HADS), EuroQol (EQ), and Zarit Caregiver Burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
165
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(190 citation statements)
references
References 36 publications
12
165
2
8
Order By: Relevance
“…This can lead to poor psychosocial outcomes including reduced quality of life (QoL), emotional and financial strain, fatigue, sleep disturbances, social isolation and an increased risk of neuropsychiatric symptoms and chronic illness [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to poor psychosocial outcomes including reduced quality of life (QoL), emotional and financial strain, fatigue, sleep disturbances, social isolation and an increased risk of neuropsychiatric symptoms and chronic illness [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, experiences vary widely [5,9] and some carers adapt and cope well throughout the disease course [2]. There is a need to identify which factors predict poor psychosocial outcomes and to develop interventions that target these specific factors and those carers most at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Attending caregiver support groups may lessen loneliness and increase the perception of support (15), as the responders in the present study used to. Findings of harmful factors to the caretaker should be reflected in clinical guidelines and programs for the management of PD (13,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…After a review of validated PD caregiving instruments [1,15,18,20] , the researchers found none that integrated all the required components for this study. The preferred survey was one devised for a mailed caregiver study, contained specific questions unique to this sample of participants, and was simple and short in design so that caregivers would be more likely to complete the questionnaire.…”
Section: Methodsmentioning
confidence: 99%